2008
DOI: 10.1359/jbmr.080610
|View full text |Cite
|
Sign up to set email alerts
|

Bone Markers Predict Cardiovascular Events in Chronic Kidney Disease

Abstract: Recent studies have indicated a link between bone metabolism and cardiovascular events in patients with chronic kidney disease (CKD). CKD is a major health problem worldwide. This study evaluates the role of noninvasive markers of bone metabolism in predicting cardiovascular morbidity (coronary artery disease, peripheral vascular disease, stroke) and mortality in patients with mild to severe forms of CKD. In a prospective cohort study, 627 patients with CKD were screened. To focus on bone metabolism, tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 46 publications
1
49
0
3
Order By: Relevance
“…This association was independent of serum calcium, phosphorus, parathyroid hormone (PTH), fetuin A, and C-reactive protein. In another study of 135 stages I through V CKD patients with limited adjustment for gender, CKD stage, serum PTH, and tartrate-resistant acid phosphatase 5b, the highest tertile of alkaline phosphatase was associated with increased risk of cardiovascular events (10).…”
Section: Discussionmentioning
confidence: 97%
“…This association was independent of serum calcium, phosphorus, parathyroid hormone (PTH), fetuin A, and C-reactive protein. In another study of 135 stages I through V CKD patients with limited adjustment for gender, CKD stage, serum PTH, and tartrate-resistant acid phosphatase 5b, the highest tertile of alkaline phosphatase was associated with increased risk of cardiovascular events (10).…”
Section: Discussionmentioning
confidence: 97%
“…Studies in renal osteopathy have produced inconclusive results with regard to the effect of renal function on serum TRACP 5b concentrations. While some studies found that TRACP 5b was not increased with renal dysfunction, 30,31 other studies showed haematologica | 2011; 96(8) that secondary hyperparathyroidism in chronic renal failure was associated with increased TRACP 5b 32 and that TRACP 5b concentration correlated inversely with glomerular filtration rate in pre-dialysis patients with chronic kidney disease. 33 The lack of a correlation between serum creatinine and TRACP 5b concentrations in this study may reflect the effect of body mass on creatinine.…”
Section: Beta (95% Ci) P Standardized Betamentioning
confidence: 99%
“…(4) Evidence suggests that vascular disease is at least partially related to poor bone health. (5)(6)(7)(8) Importantly, deviation from the normal range of serum bone biomarkers predicts an increased risk of cardiovascular events, (9) and impaired bone remodeling is associated with increased vascular calcification. (10) In the general population, individuals with osteoporosis have increased atherosclerosis and coronary artery calcification (11)(12)(13)(14) and there is an inverse relationship between coronary artery calcification and bone mineral density (BMD) in both normal and CKD patients.…”
Section: Introductionmentioning
confidence: 99%